Bloom’s Taxonomy Analyze Category: The Analysis of Students’ Analytical Skills Based on Gender (Department of Mathematics, Universitas Negeri Semarang, 2022)
This study aims to describe students' analytical skills based upon gender differences. Bloom's Taxonomy analyze category is the basis for determining the level of analytical skills. According to Bloom's Taxonomy, analytical skills consist of three cognitive processes: differentiating, organizing, and attributing. This type of research was qualitative, with the research subject as many as six students on the number material. This research was conducted on seventh-grade students at one of the junior high schools (SMP) in South Sumatra. Research subjects were determined reached from the results of initial mathematical abilities consisting of two students with high initial abilities, two medium early abilities, and one low initial ability. The study's results revealed that students’ analytical skills of girls were better than boys. Girls fulfill all cognitive processes of analytical skills. In contrast, in solving number problems, boys only achieve some of the cognitive analytical skills process.